Role of Organizational Culture in Fostering Innovation in Higher Education Institutions - Chandel, Ajay; Kaur, Jasneet (Prabandhan: Indian Journal of Management, 2023)
Managers have left no stone unturned in their quest to discover the elixir of sustainability, and they have realized that in this copycat economy, the only way to success and sustainability is â€œinnovation,â€ which determines the capability of an organization. This is why every organization â€“ start-up or established â€“ wants to be innovative. Most organizations believe that the secret to innovation is an organizational culture that encourages innovation and creativity, resulting in sustainable competitive advantage. Like all other organizations, higher education institutions should constantly focus on innovation to succeed. However, reforms in the education sector to make it more innovative are often poorly implemented. This study aimed to find out the tradeoff or gaps between the expected and perceived organizational culture-related dimensions fostering innovation in selected 280 teachersâ€™ expectations from private and public universities in Punjab, where Strategy was found to be the most critical dimension driving innovation and creativity, followed by Leadership, Innovation-Encouraging Behavior, Organizational Support, and others. The private universities assessed for this study showed the least tradeoff on all the dimensions; whereas, public universities showed the highest tradeoff on all.